Wide Area Surveillance Real-time Motion Detection Systems - Asari, Vijayan K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The book describes a system for visual surveillance using intelligent cameras. The camera uses robust techniques for detecting and tracking moving objects. The real time capture of the objects is then stored int he database. The tracking data stored in the database is analysed to study the camera view, detect and track objects, and study object behavior. These set of models provide a robust framework for coordinating the tracking of objects between overlapping and non-overlapping cameras, and recording the activity of objects detected by the system.
Background Subtraction: Theory and Practice -- Moving Cast Shadows Detection Methods for Video Surveillance Applications -- Moving Object Detection and Tracking in Wide Area Motion Imagery -- Recognizing Complex Human Activities via Crowd Context -- Event Based Switched Dynamic Bayesian Networks for Autonomous Cognitive Crowd Monitoring -- Unified Face Representation for Individual Recognition in Surveillance Videos -- Person Re-identification in Wide Area Camera Networks -- Opportunities and Challenges of Terrain Aided Navigation Systems for Aerial Surveillance by Unmanned Aerial Vehicles -- Automatic Target Recognition in Multispectral and Hyperspectral Imagery Via Joint Transform Correlation -- An Overview of Distributed Tracking and Control in Camera Networks.
Keywords: Engineering; Artificial intelligence; Computer vision; Engineering; Signal, Image and Speech Processing; Image Processing and Computer Vision; Artificial Intelligence (incl. Robotics).